The imperial examination and the college entrance examination from the perspective of affirmative action: assistance to disadvantaged examinees in China - Jinshan Yuan; Aochong Zhang (Humanities & Social Sciences Communications)
Abstract Affirmative action in China’s selective examinations arises from the pursuit of educational equity and recognition of challenges faced by disadvantaged examinees. Selective examinations, exemplified by the imperial examination (Keju) and the National College Entrance Examination (Gaokao), serve as mechanisms for social mobility. This study employs historical and policy research methods, integrating theoretical analysis with historical investigation. By integrating historical and modern contexts, the research explores how affirmative action measures have been supporting disadvantaged examinees, hoping to provide the international community with a broader understanding of over a millennium of China’s efforts to support vulnerable examinees in the examination system. Affirmative action in the imperial examination is characterized by its long duration and limited effectiveness. In the case of the Gaokao, affirmative action plays a positive role, but there is a lack of precise identification of disadvantaged candidate groups. Therefore, efforts should continue across multiple dimensions, including institutional guarantees, policy support, and resource assistance, to promote fairness in examinations and safeguard educational equity.